Editorial statement: The first five years of the European Journal of Government and Economics - Diego Varela; Giacomo Benedetto; Jose Manuel Sanchez-Santos (European Journal of Government and Economics (EJGE), 2017)
This editorial statement reflects on the experience from the first five years of the European Journal of Government and Economics and proposes some broad ideas about what we believe should be the future of the journal in the following years. The developments and ideas presented here are divided in three parts: achievements and difficulties of the past five-year period, the renewal of the editorial team, and new challenges for the future.
Keywords: 330; Academic publishing; Journal management